Osteopathia striata congenita with cranial sclerosis and intellectual disability due to contiguous gene deletions involving the WTX locus. (5th July 2012) - Holman, SK; Morgan, T; Baujat, G; Cormier‐Daire, V; Cho, T‐J; Lees, M; Samanich, J; Tapon, D; Hove, HD; Hing, A; Hennekam, R; Robertson, SP
<x xml:space="preserve">Abstract</x> Osteopathia striata congenita with cranial sclerosis (OSCS) is a skeletal dysplasia caused by germline deletions of or truncating point mutations in the X‐linked gene WTX (FAM123B, AMER1). Females present with longitudinal striations of sclerotic bone along the long axis of long bones and cranial sclerosis, with a high prevalence of cleft palate and hearing loss. Intellectual disability or neurodevelopmental delay is not observed in females with point mutations in WTX leading to OSCS. One female has been described with a deletion spanning multiple neighbouring genes suggesting that deletion of some neighbouring loci may result in abnormal neurodevelopment. In this cohort of 13 females with OSCS resulting from deletions of WTX, a relationship is observed where deletion of ARHGEF9 and/or MTMR8 in conjunction with WTX results in an additional neurodevelopmental phenotype whereas deletion of ASB12 along with WTX is associated with a good neurodevelopmental prognosis.